Using time scales to characterize phytoplankton assemblages in a deep subalpine lake during the thermal stratification period: Lake Iseo, Italy - Marti, Clelia; Imberger, J.; Garibaldi, L.; Leoni, B. (Wiley-Blackwell Publishing, Inc., 2016)
© 2015. American Geophysical Union. All Rights Reserved. A combination of field observations and 3-D hydrodynamic simulations were used to identify the phytoplankton species and to estimate the various time scales of the dominant physical and biological processes in Lake Iseo, a deep subalpine lake located in northern Italy, during a stratified period (July 2010). By ordering the rate processes time scales, we derive a phytoplankton patch categorization and growth interpretation that provides a general framework for the spatial distribution of phytoplankton concentration in Lake Iseo and illuminates the characteristics of their ecological niches. The results show that the diurnal surface layer was well mixed, received strong diurnal radiation, had low phosphorus concentrations and the phytoplankton biomass was sustained by the green alga Sphaerocystis schroeterii. The vertical mixing time scales were much shorter than horizontal mixing time scales causing a depth-uniform chlorophyll a concentration. The horizontal patch scale was determined by horizontal dispersion balancing the phytoplankton growth time scale, dictating the success of the observed green algae. The strongly stratified nutrient-rich metalimnion had mild light conditions and Diatoma elongatum and Planktothrix rubescens made up the largest proportions of the total phytoplankton biomass at the intermediate and deeper metalimnetic layers. The vertical transport time scales were much shorter than horizontal transport and vertical dispersion leading to growth niche for the observed phytoplankton. The study showed that time-scale hierarchy mandates the essential phytoplankton attributes or traits for success in a particular section of the water column and/or water body.